Adenoma of the ampulla of Vater: putative precancerous lesion. Issue 12 (December 1991) - Yamaguchi, K; Enjoji, M
Abstract : The histopathology of 12 patients with adenoma of the ampulla of Vater was examined to trace the adenoma-carcinoma sequence of the ampulla of Vater. Immunohistochemistry for carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 was also performed. Four large adenomas with mild dysplasia also had foci of moderate dysplasia while another one contained foci of severe dysplasia (intramucosal carcinoma). Immunohistochemically, adenomas of mild to moderate dysplasia had either linear CEA and CA19-9 immunoreactants at the apical portions, or fine granular immunoreactants in the cytoplasm of adenoma cells. In addition, adenomas of severe dysplasia (intramucosal carcinoma) showed a more diffuse or dense immunoreactivity for these two substances in the cytoplasm. These results are consistent with the adenoma-carcinoma sequence for the ampulla of Vater. The immunohistochemistry for CEA and CA19-9 was representative of the degree of dysplasia in the adenoma cells, but the relationship was not conclusive.